A study on the effect of film crystallinity and morphology on charge carrier concentration-dependent hole mobility in pentacene thin-film transistors: advantages of high deposition rate. (15th October 2020) - Jena, Sanjoy; Ray, Debdutta
Abstract: The combined effect of deposition rate and substrate temperature on the film crystallinity, morphology, and electronic properties of pentacene is studied. It is shown that the channel mobility in polycrystalline pentacene thin-film transistors is relatively immune to substrate temperature, and the films offer good hole mobility when grown at a high rate. This is advantageous when high throughput with low deviation in electrical parameters over devices are required. The surface morphology is characterized by atomic force microscopy measurements and the crystallinity is studied using x-ray diffraction. The effect of growth parameters on the crystalline phases of pentacene is correlated to the charge carrier transport. It is found that the field-effect mobility is primarily affected by the crystalline phases of the film rather than the grain size. The charge carrier dependence of the hole mobility is used to parameterize the dispersion (width) in the density of states (DOS) of the highest occupied molecular orbital of the films in the transistor channel region. It is found that the presence of multiple phases in the path of the charge carrier flow increases the dispersion of the DOS.